Developing adaptive political capabilities for high political uncertainty contexts :a study of strategic responses in the international operations of food firms in Latin America - de Villa, Maria Andrea (Cranfield University, 2014)
The corporate political activity field has focused on the study of political capabilities that allow firms to influence governments and regulators. Building on previous studies, this thesis examines a set of capabilities that allow host firms to adapt to rather than influence political environments. Specifically, this set of adaptive political capabilities can be used by firms to confront host country political contexts in emerging economies that share two characteristics: authoritarian regimes and weak institutions. The findings of this thesis show that host firms can develop and use adaptive political capabilities rather than political capabilities to start and sustain their operations in this type of political contexts. This entails attuning firm processes, structures, and practices to local norms and political behaviors, rather than attempting to shape the host country political environment in its own likeness. Our results suggest host firms can develop adaptive political capabilities to enhance their strategic repertoire when starting or sustaining operations in emerging economies with such characteristics. Our contribution is that by using mixed methods, we provide and test several exploratory propositions that support the conceptualization of a framework to guide the development of adaptive political capabilities by host firms and we make explicit a taxonomy of corporate adaptive political strategies that can enable firms to envision how they can adapt to host political contexts.
Keywords: non-market strategy; resource-based view; dynamic capabilities; political capabilities; corporate political activities; political strategies; internationalization; food industry